Assessing potential risks of treatment with long-term azithromycin in COPD patients: long-term oxygen users beware?. (November 2016) - Nicholson, T.; Franciosi, A.; Landers, S.; Butler, M.
Abstract Introduction Long-term daily azithromycin therapy reduces the frequency of exacerbations in chronic obstructive pulmonary disease (COPD) in a randomized controlled clinical trial setting. Concerns exist regarding arrhythmic and auditory toxicities from chronic use in the real-world setting. We hypothesized that risk factors for adverse drug reactions to azithromycin would be more frequent than previously reported, that certain specific subgroups would have different frequencies of these risk factors and that the whispered voice test would be a useful test with which to test for hearing deficits. Methods Following ethical approval, 47 consecutive hospital-based patients with a mean age 69 years ± 8.2, and with physician-diagnosed COPD (mean FEV1 45.1 ± 18 % predicted), were screened for subjective hearing impairment (screening questions and whispered voice test) and by electrocardiogram for prolonged QTc. Other potential risk factors and contraindications to long-term daily azithromycin were sought. Results In total, 38 patients (80.9 %) had at least one risk factor or contraindication to azithromycin treatment. 19 patients (40.4 % of total) had subjective hearing impairment. 17 (36.1 %) had prolonged QTc intervals. 4 patients (8.51 %) had contraindicating co-morbidities. Those on long-term oxygen therapy were significantly more likely to have at least one risk factors or contraindications to azithromycin (p  = 0.0025). Conclusion In a COPD population who would otherwise potentially be candidates for long-term daily azithromycin therapy, over 80 % had risk factors for complications from long-term daily azithromycin. Preventative treatment with long-term daily azithromycin may be appropriate for fewer COPD patients than previously thought, especially in those on long-term oxygen therapy.